2020
DOI: 10.1177/1178223420944864
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Everolimus-Based Therapy in Hormone-Receptor-Positive Metastatic Breast Cancer Patients After Progression on Palbociclib

Abstract: Background: Despite the approval of mTOR inhibitor everolimus and CDK4/6 inhibitors in the management of hormone-receptor-positive HER2 non-amplified metastatic breast cancer (HR+ HER2-MBC), the optimal sequence of therapy is unclear. There are no clinical data on efficacy of everolimus in HR+ HER2-MBC after cancer progresses on CDK4/6 inhibitors. Objective: The objective of this study is to find the efficacy of everolimus in HR+ HER2-MBC after they progress on a CDK4/6 inhibitor palbociclib. Methods: This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
(30 reference statements)
4
16
0
Order By: Relevance
“…Therefore, the survival outcomes of our study suggest that EVE-based regimens could be a reasonable choice after CDK4/6i failure, in which the optimal treatment strategies have yet to be established. These results are in line with prior retrospective studies that have reported similar PFS with EVE between CDK4/6i-exposed and unexposed patients [20], and a modest survival outcome with a median PFS of four months and a median OS of 19 months with EVE following CDK4/6i in a heavily treated patient population [21].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the survival outcomes of our study suggest that EVE-based regimens could be a reasonable choice after CDK4/6i failure, in which the optimal treatment strategies have yet to be established. These results are in line with prior retrospective studies that have reported similar PFS with EVE between CDK4/6i-exposed and unexposed patients [20], and a modest survival outcome with a median PFS of four months and a median OS of 19 months with EVE following CDK4/6i in a heavily treated patient population [21].…”
Section: Discussionsupporting
confidence: 91%
“… 57 Furthermore, recent studies showed the benefit of everolimus with CDK4/6 inhibitor treatment in ER+ metastatic BC patients. 58 …”
Section: Bcmentioning
confidence: 99%
“…A 2019 retrospective study demonstrated that first-, second-and third-line palbociclib treatment followed by subsequent hormonal therapy improved rw-PFS in patients with hormone receptor + and HER2-metastatic breast cancer [31]. In another study, Dhakal et al demonstrated that a treatment sequence of everolimus following palbociclib-progression (first, second, third and fourth line) led to improved rw-PFS [32]. RWE studies have also been conducted in emerging economies to better understand treatment sequencing.…”
Section: Treatment Sequencingmentioning
confidence: 99%